2011
DOI: 10.1007/s11425-011-4254-1
|View full text |Cite
|
Sign up to set email alerts
|

Special α-limit points and unilateral γ-limit points for graph maps

Abstract: Let G be a graph and f : G → G be a continuous map. Denote by P (f ), R(f ), SA(f ) and U Γ(f ) the sets of periodic points, recurrent points, special α-limit points and unilateral γ-limit points of f , respectively. In this paper, we show that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…For instance, sα(x) does not need to be closed and its isolated points are always periodic, which is in some contrast to the properties of ω(x). If we denote by SA(f ) (respectively, ω(f )) the union of α-limit sets of all backward branches (respectively, all ω-limit sets) of a map f and by Rec(f ) the set of all recurrent points of f , then Rec(f ) ⊆ SA(f ) ⊆ Rec(f ) ⊆ ω(f ), for every map f on the topological graph (see [32], cf. [18], [3]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For instance, sα(x) does not need to be closed and its isolated points are always periodic, which is in some contrast to the properties of ω(x). If we denote by SA(f ) (respectively, ω(f )) the union of α-limit sets of all backward branches (respectively, all ω-limit sets) of a map f and by Rec(f ) the set of all recurrent points of f , then Rec(f ) ⊆ SA(f ) ⊆ Rec(f ) ⊆ ω(f ), for every map f on the topological graph (see [32], cf. [18], [3]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…By Lemma 4.4, P Tx (x) is either a cycle of graphs or a solenoidal set Q(x). In the latter case, Q(x) ⊃ α({y i } i≤0 ) and, by results from [34], ω(f…”
Section: Preliminariesmentioning
confidence: 91%
“…It has been shown that sα-limit sets are always analytic, but not necessarily Borel [22]. If we denote by SA(f ) (respectively, ω(f )) the union of α-limit sets of all backward branches (respectively, all ω-limit sets) of a map f and by Rec(f ) the set of all recurrent points of f , then Rec(f ) ⊆ SA(f ) ⊆ Rec(f ) ⊆ ω(f ), for every map f on the topological graph (see [34], cf. [19], [4]).…”
mentioning
confidence: 99%
“…In [28] the author defines this set as the special α-limit set of x and examines them for interval maps. These sets are investigated in [46] and [45] for graph maps and dendrites. Call this Approach 2 (A2).…”
Section: Various Notions Of Negative Limit Setsmentioning
confidence: 99%
“…First introduced by Hero [28] who studied them for interval maps, γ-limit sets have since been further examined by Sun et al in [46] and [45] for graph maps and dendrites respectively. The γ-limit set of a point x, denoted γ(x), is defined by saying that, for any y ∈ X, y ∈ γ(x) if and only if y ∈ ω(x) and there exists a sequence y i ∞ i=1 in X and a strictly increasing sequence n i ∞ i=1 in N such that f ni (y i ) = x for each i and lim i→∞ y i = y.…”
Section: A Remark On γ-Limit Setsmentioning
confidence: 99%